2006
DOI: 10.4049/jimmunol.176.5.3149
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of the FcRγ Chain-Associated Human Osteoclast-Associated Receptor Enhances the Proinflammatory Responses of Human Monocytes and Neutrophils

Abstract: We have previously described the human osteoclast associated receptor (hOSCAR), expressed in all cells of the myeloid lineage, and its immune functions. This receptor, which associates with the FcRγ chain to transduce an activating signal, induces calcium flux in monocytes and dendritic cells, and modulates specific responses of dendritic cells. In this study, we have examined the effects of hOSCAR ligation on various proinflammatory responses of monocytes and neutrophils. Monocytes stimulated via hOSCAR ligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 37 publications
4
56
3
1
Order By: Relevance
“…Unlike the DAP12-associated TREM-1 [31, 32], CD300e was not upregulated upon monocyte activation via TLR4 (data not shown), thus resembling the FcRg-associated receptor hOSCAR [27]. CD300e ligation induced a rapid intracellular calcium mobilization, as well as the production of ROS, supporting that this receptor may regulate the microbicidal activity of monocytes [33].…”
Section: Discussionmentioning
confidence: 96%
“…Unlike the DAP12-associated TREM-1 [31, 32], CD300e was not upregulated upon monocyte activation via TLR4 (data not shown), thus resembling the FcRg-associated receptor hOSCAR [27]. CD300e ligation induced a rapid intracellular calcium mobilization, as well as the production of ROS, supporting that this receptor may regulate the microbicidal activity of monocytes [33].…”
Section: Discussionmentioning
confidence: 96%
“…OSCAR expression in human monocyte-derived DCs (11) and monocytes (30) was suggested to support cell survival in the absence of growth factors via induction of antiapoptotic molecules Bcl-2 and Bcl-x L through PI3K and ERK signaling. In our study, the DCs plated on ColI/II showed prolonged viability in the absence of the essential growth factor, GM-CSF, indicating that OSCAR could play an important role in cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…endothelial cells, macrophages, neutrophils, monocytes, and monocyte-derived dendritic cells (17,18). Consequently, OSCAR is likely to contribute to the regulation of a wide variety of cellular functions in different cells, including roles in adhesion, activation and enhancement of proinflammatory cascades, cellular recruitment, and prevention of apoptosis.…”
Section: Significancementioning
confidence: 99%